2012
DOI: 10.1590/s0482-50042012000400009
|View full text |Cite
|
Sign up to set email alerts
|

Diretrizes para prevenção e tratamento da osteoporose induzida por glicocorticoide

Abstract: Glucocorticoids (GC) are used in almost all medical specialties, and approximately 0.5% of the general population of the United Kingdom receives those medications. With the increased survival of patients with rheumatological diseases, morbidity secondary to the use of those medications represents an important aspect of the management of our patients. The incidences of vertebral and non-vertebral fractures are elevated, ranging from 30% to 50% of the individuals on GC for over three months. Thus, osteoporosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
8

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(22 citation statements)
references
References 85 publications
(125 reference statements)
0
14
0
8
Order By: Relevance
“…It frequently affects children with diffuse connective tissue diseases [21,22], inflammatory bowel diseases [23], chronic renal diseases [24,25], hematological malignancies [26,27,28,29], or solid tumors [30]. Systemic glucocorticoid treatment is associated with an initial increase in bone resorption and a subsequent reduction of bone formation, leading to decreased peak bone mass, microarchitectural deterioration and increased fracture risk [31,32,33,34]. There is good evidence that oral glucocorticoids, mainly when used for more than 3 months and at doses greater than 5-7.5 mg/day of prednisone (or equivalent), increase the risk of fragility fractures [31,32,33].…”
Section: Bisphosphonate Use In Pediatric Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…It frequently affects children with diffuse connective tissue diseases [21,22], inflammatory bowel diseases [23], chronic renal diseases [24,25], hematological malignancies [26,27,28,29], or solid tumors [30]. Systemic glucocorticoid treatment is associated with an initial increase in bone resorption and a subsequent reduction of bone formation, leading to decreased peak bone mass, microarchitectural deterioration and increased fracture risk [31,32,33,34]. There is good evidence that oral glucocorticoids, mainly when used for more than 3 months and at doses greater than 5-7.5 mg/day of prednisone (or equivalent), increase the risk of fragility fractures [31,32,33].…”
Section: Bisphosphonate Use In Pediatric Patientsmentioning
confidence: 99%
“…Systemic glucocorticoid treatment is associated with an initial increase in bone resorption and a subsequent reduction of bone formation, leading to decreased peak bone mass, microarchitectural deterioration and increased fracture risk [31,32,33,34]. There is good evidence that oral glucocorticoids, mainly when used for more than 3 months and at doses greater than 5-7.5 mg/day of prednisone (or equivalent), increase the risk of fragility fractures [31,32,33]. A recent systematic review and meta-analysis of glucocorticoid-induced osteoporosis in children reported incident clinical fracture rates from 2 to 33%.…”
Section: Bisphosphonate Use In Pediatric Patientsmentioning
confidence: 99%
“…A primária divide-se em dois tipos: tipo I atinge as mulheres por estar associada à pós-menopausa pela diminuição abrupta na produção de estrogênio e atinge predominantemente o osso trabecular, e tipo II, associada ao envelhecimento, também conhecida como osteoporose senil, e aparece por deficiência crônica de cálcio. A secundária está relacionada a pessoas portadoras de doenças renais, endócrinas, hematológicas ou que fazem uso de alguns tipos de medicamentos 4,7,17 .…”
Section: Discussionunclassified
“…Assim, o uso preventivo dessas suplementações, visa diminuir o impacto do uso dos GC sobre a densidade mineral óssea e o risco de fraturas 43 .…”
Section: Discussionunclassified